2005
DOI: 10.1021/jf052040y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lectins on the Transport of Food Factors in Caco-2 Cell Monolayers

Abstract: The effect of three plant lectins, soybean lectin (SBA), Japanese jack bean lectin (CGA), and wheat germ lectin (WGA), on the transport of various food factors, such as isoflavones, quercetin, dipeptides, and calcium ions, were investigated by use of an intestinal tract model, Caco-2 cell monolayers. The lectins increased the isoflavone transport but had no effect on aglycon transport. SBA increased the transport of quercetin glycosides, whereas CGA and WGA had no effect. The lectins increased the transport of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…In this study, ileal mucosa DAO in piglets fed 0.1, 0.15 or 0.2% SBA decreased, and plasma d -lactic acid content was enhanced, which indicated that the intestine injured by 0.1–0.2% SBA increased the epithelial permeability. A previous study showed that SBA (90 μg/mL) slightly increased the values with quercetin glycosides or calcium ions [18], which is consistent with this study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, ileal mucosa DAO in piglets fed 0.1, 0.15 or 0.2% SBA decreased, and plasma d -lactic acid content was enhanced, which indicated that the intestine injured by 0.1–0.2% SBA increased the epithelial permeability. A previous study showed that SBA (90 μg/mL) slightly increased the values with quercetin glycosides or calcium ions [18], which is consistent with this study.…”
Section: Discussionsupporting
confidence: 93%
“…7). These findings are in agreement with results published by Ohno et al [56], who found increases in the TER of Caco-2 monolayers after incubating them for 4 h with quercetin glycosides at 80 lM. However, other authors detected no significant effects of raspberry extracts containing various anthocyanins, ellagitannins, and hydroxycinnamic acid derivatives on the TER of Caco-2 monolayers [57].…”
Section: Influence Of Polyphenols On Tersupporting
confidence: 93%
“…It was also reported that garlic (A. sativum) lectin maintained its activity in the intestines and activated immunoreactivity when orally administered to mice (Clement et al, 2010). We have shown that lectins contained in foodstuff had modulating effects on the transport system of human intestinal Caco-2 cell monolayers (Ohno et al, 2006;Yamamoto et al, 2013;Nemoto et al, 2015). Thus, plant lectins can be considered as physiologically active ingredients in food resources.…”
Section: Discussionmentioning
confidence: 79%